Transformasi Budaya Organisasi melalui Inovasi Berkelanjutan: Studi Kasus Organisasi Pemerintah dalam Menghadapi Tantangan Industri 4.0 - Maggara, Tomi Satria; Frinaldi, Aldri (Lembaga Yasin AlSys, 2024)
Transforming organizational culture through continuous innovation is an important issue in the modern business context. This innovative approach plays a key role in shaping company performance, employee satisfaction and competitiveness in the global marketplace. This article explores the impact of transforming organizational culture through continuous innovation and provides insights into strategies and best practices that can be adopted by companies in facing the challenges of Industry 4.0. The research method used in this article is a qualitative approach with a descriptive approach. Through case studies on leading technology companies, this research seeks to understand how innovative practices are implemented and integrated into organizational culture. In-depth analysis of the case study provides deep insight into the process of organizational culture transformation through continuous innovation. The results of the discussion show that organizational culture transformation through sustainable innovation has a significant impact on company performance, employee satisfaction and competitiveness in the global market. Employees who feel supported in innovation tend to be more engaged and productive, while companies that have an innovative culture have a greater competitive advantage. Thus, transforming organizational culture through continuous innovation is the key to achieving growth and sustainability in the Industry 4.0 era.